2005
DOI: 10.1002/aoc.792
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of diphenylarsinic acid in human and environmental samples by HPLC-ICP-MS

Abstract: A simple, rapid and robust analytical method for determining diphenylarsinic acid in human and environmental samples was developed based on a combination of hydrophilic polymer-based gelpermeation high-performance liquid chromatography (HPLC) and inductively coupled plasma mass spectrometry (ICP-MS). Hair and nail samples were digested with alkali, and liberated diphenylarsinic acid (derivative) was extracted with diethyl ether, redissolved in water and injected for HPLC-ICP-MS analysis. Human urine, groundwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Although SEC is most commonly used for the separation of relatively large compounds such as polymers and biopolymers, it can be used for the separation of compounds of intermediate molecular weight as well. For example, Shibata et al [39] determined diphenylarsinic acid in urine, groundwater, and soil extract samples by SEC-ICP-MS. The analysis was performed with a sub-parts-per-billion detection limit.…”
Section: Particle Size Fractionationmentioning
confidence: 99%
“…Although SEC is most commonly used for the separation of relatively large compounds such as polymers and biopolymers, it can be used for the separation of compounds of intermediate molecular weight as well. For example, Shibata et al [39] determined diphenylarsinic acid in urine, groundwater, and soil extract samples by SEC-ICP-MS. The analysis was performed with a sub-parts-per-billion detection limit.…”
Section: Particle Size Fractionationmentioning
confidence: 99%
“…All products were crystallized from ethanol. 1 13 C NMR data and other properties of the triarylarsines are given in Table 1.…”
Section: Triarylarsinesmentioning
confidence: 99%
“…1 Analysis showed that the arsenic was present almost entirely as diphenylarsinic acid 1 and was thus very unlikely to have a natural origin. The source of this compound to the ground water supplying the well is unknown, although the most likely explanation is that arsenical war gases or their precursors were dumped and buried in the area during, or immediately following, the World war II.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) was carried out. Research activities have included the development of analytical techniques, [2] monitoring of the concentrations of DPAA and its transformation products in human urine and groundwater, [3,4] studies of the absorption and metabolism of DPAA by plants, [5,6] studies of the toxicodynamics of DPAA in experimental animals [7,8] and studies aimed at elucidating the mechanism of DPAA's toxicity. [9] During recent measurements using liquid chromatographyinductively coupled plasma-mass spectrometry (LC-ICP-MS) of DPAA and related arsenicals in groundwater samples, we detected unknown arsenic species that appeared to be derived from DPAA.…”
mentioning
confidence: 99%